Strategi Integrasi Program Unggulan Public Speaking dan Kurikulum Merdeka dalam Manajemen Kurikulum di SMP IT Shidqia Islamic School - Farhan Fitrian; Rugaiyah; Masduki Ahmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The implementation of the Merdeka Curriculum offers opportunities for educational institutions to develop curricula that align with the unique characteristics and needs of their students. SMP IT Shidqia Islamic School, as an integrated Islamic educational institution, has several flagship programs that emphasize Islamic values and character building. This study aims to explore strategies for integrating the school’s flagship programs with the Merdeka Curriculum within the framework of curriculum management. A descriptive qualitative method with a case study approach was used. Data were collected through interviews, observations, and document analysis. The findings indicate that the integration is carried out by aligning the school’s vision with the learning objectives of the Merdeka Curriculum, strengthening the role of teachers as facilitators, and implementing flexible lesson module development that includes local content and Islamic values. This integrative strategy is considered effective in enhancing curriculum relevance and reinforcing the school’s identity as a value-based educational institution. The study recommends ongoing professional development for teachers and strengthened collaboration among school stakeholders to optimize contextual and sustainable curriculum management.